Use of Autologous Platelets for Lamellar Macular Hole Repair. (19th May 2019) - Gonzalez, Andres; Amin, Sarina; Iqbal, Omar; Potter, Stephen Myles; Khurshid, Syed Gibran
Abstract : The consensus of lamellar macular hole repair generally entails vitrectomy with internal limiting membrane with/without epiretinal membrane peeling with gas tamponade, although the risk of a full thickness macular hole remains. In this case report, we investigate the role of the regenerative properties of autologous platelets in the repair of a lamellar macular hole with pars plana vitrectomy, an autologous platelet plug, and 12% C3F8 without prone posturing. All three patients in this case report experienced visual improvement along with anatomic closure of the lamellar macular hole. Further randomized studies with larger sample sizes will contribute to the existing data regarding this procedure and its outcomes.